Strengthening Motivation and Strategies for Doctoral Studies Success: A Community Service to Doctoral Students through Post Graduate Meet-Up - Putra, Eka (Bhandar: Harvesting Community Service in Asia, 2024)
This community service activity was carried out with the aim of providing insights, motivation, and strategies to doctoral students in facing academic challenges. The program was conducted in the form of an interactive discussion at the Post Graduate Meet-Up at the Faculty for Language Studies and Human Development, Universiti Malaysia Kelantan. An expert speaker, who is both an academic and practitioner, shared their experiences in completing doctoral studies, emphasizing time management, research strategies, and learning motivation. The results of the activity showed increased awareness among students about the importance of planning, time management, and a strong support system in the doctoral study process. Additionally, students received practical tips to improve the effectiveness of their research.